2023
DOI: 10.1073/pnas.2212650120
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of clonal cooperative architecture in multispecies biofilms and the spatial ecology of predation

Abstract: Biofilm formation, including adherence to surfaces and secretion of extracellular matrix, is common in the microbial world, but we often do not know how interaction at the cellular spatial scale translates to higher-order biofilm community ecology. Here we explore an especially understudied element of biofilm ecology, namely predation by the bacterium Bdellovibrio bacteriovorus . This predator can kill and consume many different Gram-negative bacteria, including Vibrio chole… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 105 publications
1
5
0
Order By: Relevance
“…Growing data support the hypothesis that spatial organization is an essential determinant in shaping microbial communities and can further dictate important community-based behaviors [4,5,35,[51][52][53][54][55][56][57]. In this study, we found that P. aeruginosa motility plays a vital role in shaping the biogeography in polymicrobial environments with S. aureus.…”
Section: Discussionsupporting
confidence: 75%
“…Growing data support the hypothesis that spatial organization is an essential determinant in shaping microbial communities and can further dictate important community-based behaviors [4,5,35,[51][52][53][54][55][56][57]. In this study, we found that P. aeruginosa motility plays a vital role in shaping the biogeography in polymicrobial environments with S. aureus.…”
Section: Discussionsupporting
confidence: 75%
“…If lysogens preferentially disperse because they originate in peripheral biofilm regions of low cell density, we would also predict that within larger WT biofilm clusters to which phages have been added, there should be peripheral regions of reduced cell packing from which dispersed lysogens are mostly derived, and therefore in which the within-biofilm lysogen frequency should quantitatively match the liquid effluent lysogen frequency. We assessed this prediction by segmenting the total and the lysogenized cell volumes within WT biofilm exposed to phages for 24 h. We calculated the localized cell-cell packing as was done above and in previous reports( 12 , 13 ), and we analytically binned the segmented biomass according to the localized cell packing in the vicinity, seeking to find a cell-packing threshold below which the lysogen frequency in the effluent matched the within-biofilm frequency ( Figure 3B,C ). We performed this analysis iteratively for different density thresholds and determined that lysogen abundance is accurately reflected by the biofilm composition at cell volume fractions of 0.3 and lower, which can generally be found in a belt around the biofilm exterior and also reflects the median cell packing at which lysogens tend to be located after the initial wave of phage activity along the biofilm exterior ( Figure 1E , Figure 2C) .…”
Section: Resultsmentioning
confidence: 99%
“…This mode of group formation among bacteria is ubiquitous in both natural and human-made environments, and a primary function of collective growth is protection against threats bacteria encounter, such as invading competitors, diffusible antimicrobial compounds, predatory bacteria, and phages (9)(10)(11). The cellular scale dynamics of group protection against these threats are not always well known, particularly for phages and predatory bacteria (12)(13)(14)(15). Complementing prior work with cellular scale resolution observation of phage-biofilm interactions can provide crucial insight into the driving mechanisms of these interactions at the scale on which microbial phenotypes directly manifest.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices can be employed to create model, micro-environments in which single bacteria may be observed for extended periods of time. These engineered systems provide a test-bed for ecological theories of microbial population and community dynamics [38] providing insight into bacterial competition within soil-like porous environments [10], the phage susceptibility of microbial communities within structured environments [42], the protection from predation offered by a structured biofilm [51], among other topics. Recently, Koldaeva et al studied the competitive dynamics of two effectively neutral strains of E. coli grown within open-ended microchannels [26].…”
Section: Introductionmentioning
confidence: 99%